Design and Analysis of Combined Valve Spool with Linear Flow Coefficient - Changxiong Xie; Heng Su; Jun Yang; Zhongjing He (Journal of Engineering)
The orifice flow model is generally established based on the turbulent state, and the flow discharge is considered to be a constant value. In fact, the flow discharge has obvious nonlinearity under the condition of small opening and small pressure difference of the valve port, which makes the electro-hydraulic servo system more difficult to control. In order to improve the nonlinearity of the flow discharge, the paper designed different spool profile, such as the arc combined spool profile, the power curve combined spool profile, the index curve combined spool profile, and the mixed curve combined spool profile, and analyzed the flow discharge through CFD simulation and experiment. The results show that the flow discharge of the mixed curve combined spool is more linear and the residual sum of squares is the smallest, which is 2.56 × 10−3 under CFD numerical simulation and 3.26 × 10−4 under experiment. The combined spool has better linear characteristics, which can improve the control performance of the electro-hydraulic servo valve.